Integrated Non-Digital Media Innovation ‘Space Capsule’ to Train Spatial Visualization Skills in Solid Geometry for Students - Alia, Hilma; Lisnani, Lisnani; Widyawati, Hesti; Walker, Justin; Azhar, Riza Haikal (Mosharafa: Jurnal Pendidikan Matematika, 2026)
Tujuan penelitian ini menghasilkan media pembelajaran non-digital terintegrasi bernama "Kapsul Ruang" untuk melatih kemampuan visualisasi spasial materi bangun ruang siswa SMP. Studi ini dirancang menggunakan pendekatan model 4D, yang mencakup fase Define, Design, Develop, dan Disseminate yang melibatkan validator ahli materi dan media, serta siswa SMP sebagai subjek uji coba melalui tahapan one-to-one, small group, dan field test. Informasi dikumpulkan serta dievaluasi berdasarkan standar validitas, kegunaan praktis, dan dampak efektif dari bahan ajar non-digital yang sedang dalam proses pembuatan. Media non digital terbukti memiliki tingkat kevalidan 85% dengan kategori sangat valid, kepraktisan tinggi dengan persentase 89,3%, dan efektif meningkatkan pemahaman konsep geometri tiga dimensi, terutama bagi sekolah dengan keterbatasan akses teknologi digital. Media non digital ini berimplikasi bagi pembelajaran matematika sebagai sepaket media pembelajaran dengan integrasi pendekatan visual, manipulatif, dan game-based learning sehingga yang memberikan alternatif solusi praktis yang responsif. The purpose of this study is to produce an integrated non-digital learning media called "Space Capsule" to train the spatial visualization ability of junior high school students' spatial geometry material. The study was crafted using the 4D development framework, which includes the stages of Define, Design, Develop, and Disseminate used by involving expert validators of material and media, as well as junior high school students as trial subjects through one-to-one, small group, and field test stages. Information was gathered and evaluated based on the standards of validity, practicality, and effectiveness for the non-digital media currently in development. Non-digital media is proven to have a validity level of 85% with a very valid category, high practicality with a percentage of 89.3%, and is effective in increasing the understanding of three-dimensional geometry concepts, especially for schools with limited access to digital technology. This non-digital media has implications for mathematics learning as a package of learning media with an integration of visual, manipulative, and game-based learning approaches, thus providing alternative responsive practical solutions.